Improving access to palliative care for persons with Parkinson disease - Ramanathan, Usha; Tanuseputro, Peter (Annals of Palliative Medicine, 2020)
Growing literature suggests that persons with Parkinson disease have increased palliative care needs. Specifically, non- motor symptoms (such as pain) are often underrecognized and undertreated, there is inadequate psychosocial support, there are increased rates of nursing home placement and hospitalization especially in the last year of life, and caregivers face increased burden of responsibility (1). There is established evidence that palliative care improves quality of life for persons with Parkinson disease (2). There are consensus statements supporting the early integration of palliative care into neurological care for persons with Parkinson disease, with involvement of multidisciplinary teams, as well as involvement of patients and caregivers in advance care planning (3).